Local people’s perception on vandalism behaviour at ecotourism site in Kiulu Farmstay - Maratin, Jannefer (2018)
Vandalism is a challenge towards one place or location in development. Everyone that is involved in ecotourism industry especially the owner of the business should take into account on minimising vandalism behaviour at ecotourism site. This study was conducted to determine the level of understanding about vandalism from Kiulu Farmstay community point of view and the direct and indirect effects on their income. The data was collected qualitatively using semi-structure, face to face interview. A small group of six villagers were interviewed from the surrounding villages in Kiulu Farmstay. The finding of this study shows that the locals are aware about the effect of vandalism as a threat to their income. Besides, male villagers are more aware about vandalism issues compared to female. This is because most male became local tourist guide and they have seen the effect of vandalism in Kiulu Farmstay. However, the finding of this study may have other implications on other group on practical basis.